Re-imagining doctor-patient relationships in an African context: a transformative educational perspective - Ras, Tasleem (Department of Health Sciences Education, 2023)
Clinician-patient relationships are central to health care, health systems and medical education. Current educational practice of doctor-patient relationships emerged from an episteme rooted in a biomedical understanding of disease, having epistemic and pedagogical roots in Global North contexts. The thesis offers an analysis of clinician-patient relationships that includes medical ethics, communication skills, and the development of the widely accepted (in Family Medicine) Biopsychosocial model of the clinical consultation. Using a South African clinical postgraduate Family Medicine training programme as a case study, this project answered two central research questions: (i) How do students learn to navigate relationships with patients in this training programme? And (ii) Can we develop an educational model of doctor patient relationships based on local experiences? Mezirow's transformative learning theory, Mbiti's conceptualisation of Ubuntu as an African philosophy, and Foucault's thoughts on structural power provided a conceptual framework. Aim The project aimed to understand the process of student learning about the doctor-patient encounter and to develop a model for teaching about the doctor-patient relationship. Methodology A qualitative longitudinal case study was conducted, drawing data from postgraduate students, educators, and patients. Data was collected from educational, clinical, and reflective activities, and analysed thematically using an inductive approach. Findings The key themes describe students' learning in relation to critical self-awareness, contextual awareness, the dialogic nature of learning, and the impact of transformed perspectives. Patients valued that their patient-hood and personhood were validated, and educators highlighted the theme that vulnerability has pedagogical implications. A new perspective of power dynamics in the clinical encounter is described and an Ubuntu-inspired episteme and pedagogy is synthesised from the findings. Conclusion This decolonial project provides evidence and proposes a model for incorporating an indigenous philosophy (Ubuntu) into mainstream health sciences education. Recommendations are made for educational and clinical practice, as well as future research.